2011
DOI: 10.1089/jop.2010.0155
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular Pharmacokinetics of a Crystalline Lipid Prodrug, Octadecyloxyethyl-Cyclic-Cidofovir, for Cytomegalovirus Retinitis

Abstract: Purpose: To evaluate the intraocular pharmacokinetics of octadecyloxyethyl-cyclic-cidofovir (ODE-cCDV) after intravitreal injection into rabbit eyes. Methods: Twenty-seven New Zealand red rabbits (27 eyes) received intravitreal injections of 14 C-labeled ODEcCDV (100 mg drug suspended in 5% dextrose), and ocular tissues were collected from 3 rabbits at each predetermined time point (1 h, 1 day, 3 days, 1 week, 2 weeks, 3 weeks, 5 weeks, and 9 weeks) after the injection. The eye globes were enucleated, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Retinal pigment epithelium (RPE) cells display high membrane lipophilicity and tight junctions. So far, different approaches have been employed to enhance permeability of CDF such as lipid prodrugs 14 or transporter-targeted prodrugs of cCDF 1 . However, individually, these approaches have exhibited limited advantages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Retinal pigment epithelium (RPE) cells display high membrane lipophilicity and tight junctions. So far, different approaches have been employed to enhance permeability of CDF such as lipid prodrugs 14 or transporter-targeted prodrugs of cCDF 1 . However, individually, these approaches have exhibited limited advantages.…”
Section: Discussionmentioning
confidence: 99%
“…In order to resolve such problems, researchers have synthesized lipid conjugates of cCDF (octadecyloxyethyl–cCDF) for intraocular injection to improve its vitreal half-life, bioavailability, and antiviral efficacy. 14 However, the major limitation of lipid conjugates is the higher retention in lipid bilayer of plasma membrane and inability to translocate into the cytoplasm due to which it is not effective in treating deeper tissue infection such as CMV retinitis. Moreover, the low aqueous solubility of lipid prodrugs can further restrict the application of this approach.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, we showed that intravitreal injection of crystalline lipid prodrugs of small molecules, such as antiviral and antiproliferative nucleosides can be an effective strategy for the sustained delivery of drugs to the posterior segments of the eye. 5,6,8 In a recent study, we found that hexadecyloxypropyl cytarabine cyclic 3Ј,5Ј-monophosphate can be hydrolyzed to its noncyclic form, hexadecyloxypropyl-phosphocytarabine, which is water soluble and forms micelles (Cheng L, et al, unpublished data, 2011). We hypothesized that the cyclic form of HDP-cCDV could also be hydrolyzed in vitreous fluid, converting a significant portion of HDP-cCDV into HDP-CDV before reaching the retina.…”
Section: Discussionmentioning
confidence: 99%
“…After injection, four rabbits at each time point (days 1, 3, 7, and 14 and week 5) were euthanized and the aqueous humor, iris, ciliary body, vitreous, retina, and choroid were sampled after eye globe enucleation, as we previously described. 8,9 For retina and ciliary body, the samples were divided into two, one for total radioactivity counting with scintillation and the other for metabolite study by HPLC/MS. The vials were kept at Ϫ80°C until further analysis.…”
Section: Determining the Hdp-cdv Dose For Pharmacokineticmentioning
confidence: 99%
See 1 more Smart Citation